A Review of Conductivity of Conductive Polymers; Polyaniline (Pani) and its Nanocomposites - Assem, Humphrey Darkeh; Agyei, Mensah Samuel; Tamakloe, Reuben Yao; Nkum, Robert K. (European Journal of Applied Sciences, 2024)
Doped and non-doped conducting polymers represent two distinct categories within the realm of conductive polymers. The conductivity observed in non-doped conjugated polymers is attributed to the presence of a conductivity band resembling that of metals. This conductivity arises from a specific molecular configuration, wherein three out of four valence electrons undergo localized sp2 hybridization, forming robust sigma bonds. The remaining unpaired electron of each carbon atom occupies a Pz orbital, which, upon overlap with adjacent Pz orbitals, creates a pi bond. The resulting delocalization of pi electrons facilitates conductivity, albeit at a relatively modest level. The demand for high-performance materials is particularly pronounced in mobile structural applications and the energy storage sector, encompassing aerospace and space exploration vehicles, unmanned aerial vehicles (UAVs), energy-efficient air and ground vehicles, satellites, smartphones, photovoltaic cells, and flexible electronics. Notably, advancements in electrochemical energy storage materials have been directed toward enhancing ion-storage capacity and cycle life. This review delves into the intricacies of electrical conductivity within conducting polymers, with a specific focus on polyaniline (PANI) and its emeraldine-based composites. The investigation encompasses various experimental configurations, culminating in the assertion that the electrical conductivity of conducting polymers is intricately linked to their intrinsic properties, doping mechanisms, and preparation techniques, including considerations of concentration and molecular weight. The utility of conducting polymers, particularly exemplified by polyaniline, extends to a wide array of technical applications, underscoring the ongoing research interest in optimizing their conductivity. Polyaniline's conductivity can be modulated through doping or reduction processes, while the incorporation of nanoparticles offers avenues for achieving enhanced conductivity. Moreover, the exploration of thermoelectric energy conversion holds promise for harnessing waste heat, thus further amplifying the relevance of conducting polymers in contemporary technological landscapes.